2020
DOI: 10.1101/2020.05.06.20093641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sudden death in patients with sleep apnea: a systematic review and meta-analysis

Abstract: Background: Over 1 billion individuals across the globe experience some form of sleep apnea, and this number is steadily rising. OSA can negatively influence ones quality of life (QOL), while also increasing their risk of mortality from many causes. However, the association between OSA and mortality has not been comprehensively and thoroughly explored. This meta-analysis was conducted to conclusively estimate the risk of death for all-cause mortality and cardiovascular mortality in OSA patients. Study Design… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Sleep problem is a general issue that disturbs modern society (Chattu et al, 2018). Multiple studies have found that poor sleep is associated with many negative health outcomes, including cognitive impairment (Killgore, 2010;Bubu et al, 2017), mood disorders (Hertenstein et al, (Irwin, 2015) and death (Vaccaro et al, 2020;Heilbrunn et al, 2021). Although medication is a common treatment for sleep disorders, it can cause side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep problem is a general issue that disturbs modern society (Chattu et al, 2018). Multiple studies have found that poor sleep is associated with many negative health outcomes, including cognitive impairment (Killgore, 2010;Bubu et al, 2017), mood disorders (Hertenstein et al, (Irwin, 2015) and death (Vaccaro et al, 2020;Heilbrunn et al, 2021). Although medication is a common treatment for sleep disorders, it can cause side effects.…”
Section: Introductionmentioning
confidence: 99%